IDENTIFYING COMPOSITIONAL INSTRUMENTS IN A BILINGUAL PICTURE BOOK FOR LANGUAGE LEARNING - Mufida, Nisa Hanum; Ningsih, Harni Kartika (LLT Journal: A Journal on Language and Language Teaching, 2022)
Bilingual picture books are one of the materials in joint-reading activities between adults and pupils. When using picture books, adults face difficulty conveying meaning from the book to children. Therefore, this paper investigates the compositional elements of a bilingual picture book and provides an understanding of exploring a picture book to create meaningful reading activities. This case study employs a multimodal discourse analytical approach to understand the placement of the visual resources and the dual text of a bilingual picture book entitled Kina Punya Teman Baru. The result shows the compositional instruments tend to attract the reader's focus on the characters and the continuity of the storyline. The tendency of using co-located backgrounds along with the simple bull eye focus of images directs readers to the actions and emotions experienced by the character. Visual elements in a bilingual picture book are put in a contextualized setting offering readers the to explore the particular image. This bilingual picture book uses Indonesian as L1 and English as L2. The composition of the verbal text layout indicates that this bilingual picture book is intended for pupils speaking Indonesian and are willing to learn English, but they still require scaffolding in accessing the language being learned.